Exploring the pedagogical impact of “Dummies in Communication” on 21st century learners - Kee, Li Li; Mohd Nasir, 'Adnin Hanan; Rosli, Nur Aina Rodhiah; Abang Taufik, Dayang Farahany; Abu Shahni, Ain Sofia (2025)
“Dummies in Communication” is an innovative teaching and learning resource designed to simplify the understanding of communication skills, particularly for educators and learners in 21st-century classrooms. The book highlights creative strategies to enhance communication competence through interactive and learner-friendly content. The book comprises six engaging chapters: “Chapter 1: Hello! and Goodbye!” introduces basic greetings and parting expressions to set the tone for polite and effective communication; “Chapter 2: Turn-Taking Skills” focuses on how to initiate, maintain and end conversations smoothly; “Chapter 3: Negotiation Skills” teaches strategies to reach mutual understanding in everyday discussions; “Chapter 4: Interjections” explores the use of expressive words that convey emotion and add flavour to speech; “Chapter 5: Expressing Feelings” helps learners articulate emotions clearly and appropriately; and “Chapter 6: Colloquialisms” introduces informal language commonly used in daily conversation for more natural and relatable interactions. A key innovation in this book is the integration of QR codes that allow readers to scan and instantly access real-life recorded conversations. This feature bridges theory and practice, enabling readers to listen, observe and reflect on authentic communication scenarios. By incorporating technology, the book encourages flexible, multimodal learning that supports diverse learning styles. Combining clear explanations, engaging visuals and hands-on activities, Dummies in Communication empowers educators to adopt more interactive, student-centred communication techniques. This timely resource exemplifies how digital tools can transform educational experiences through innovation.